La vulnérabilité sociale et territoriale des centres des petites villes : quels enjeux pour l’action publique et associative ? - Christophe Quéva; Anaïs Béji; Marie Duchêne; Félicie Mortier; Antoine Torre; Martin Valcke (Espace populations sociétés, 2023)
Beyond the variety of their situations, French small cities are marked by demographic, social and economic weaknesses that make them socially and territorially vulnerable, particularly in the municipality center and the town center. Based on a sample of 439 municipalities of less than 20,000 inhabitants, beneficiaries of the "Petites villes de demain" or "Action Cœur de ville" programs, 69% of these cities experienced a decrease of their population between 2013 and 2018, 88% of them had a share of vacant housing higher than the French average and 92% had a share of people over 65 years old higher than the national average. However, these trends must be distinguished from one territory to another, depending on the regional and local contexts, and also on the way in which local actors, whether public or associative, take account of these fragilities. Indeed, any analysis in terms of vulnerability implies taking into account the capacity for resistance or recovery on the part of the populations concerned, and the public actions or local strategies implemented. How can we use the notion of vulnerability to consider the dynamics of small cities, between attractiveness and ageing, revival and devitalisation, fragility and resilience? And to what extent do local actors integrate these situations of vulnerability into their strategies? This text starts from a theoretical discussion on the notion of vulnerability, approached in its social and territorial dimensions, to propose a measurement and an exploratory cartography of the fragility of small French cities, considered on the level of their town center. A local field study of two small cities in the Eure-et-Loir region (the small town of Nogent-le-Rotrou and the market town of Authon-du-Perche) highlights the interplay of actors at work and considers the vulnerabilities identified as potential resources for the development of the territories.